BIOPESTICIDES TO CONTROL THE GROWTH OF A STORAGE PEST SITOPHILUS ORYZAE (L.) - SHOBHA MISHRA; R. K. NIGAM (The Bioscan, 2011)
Sitophilus oryzae L., a storage pest of wheat grains is normally managed by the application of DDT which, however, remains in the wheat grain, even after cleaning, and affects human health. The present study has used to biopesticides, viz., extracts of black peppercorns and of cinnamon bark, to control the growth of this pest. These were extracted in diethyl ether and alcohol, and then after wheat grains were soaked in the extract for 30 minutes before the adults of Sitophilus oryzae were introduced into the treated grains. It was found that the biopesticide were able to effectively control the pests. Surprisingly the mortality rate of the pest was found to be higher at low concentration and lower at higher concentration of the extracts. This was due to the fact that the adult pests were able to escape the pesticidal effect by adhering to the sides and lids of the jar and not feeding treated grains. The extracts made in alcohol found to be more effective.